Cumin, Camels, and Caravans : A Spice Odyssey - Nabhan, Gary Paul (Book collections on Project MUSE., 2014)
Gary Paul Nabhan takes the reader on a vivid and far-ranging journey across time and space in this fascinating look at the relationship between the spice trade and culinary imperialism. Drawing on his own family's history as spice traders, as well as travel narratives, historical accounts, and an ethnobotanical exploration of spices and their uses, Nabhan describes the critically important roles that Semitic peoples and desert floras had in setting the stages for globalized spice trade. Traveling along four prominent trade routes-the Silk Road, and the Frankincense Trail.